Pentingnya Kontribusi Orang Tua Terhadap Lembaga Pendidikan Dalam Peningkatan Mutu Sekolah - Clarisa Ayu Aprilia; Novia Ayya Shofia; Wann Nurdiana Sari (J-CEKI : Jurnal Cendekia Ilmiah, 2021)
The purpose of this study was to determine the importance of the contribution of parents to educational institutions in improving school quality. The focus of this problem is so that all parents out there know the role that parents should give to their children. That parents play a very important role in contributing to educational institutions because to achieve good quality education, the role of parents is needed to guide their children in the education process. The educational process of children is not only the responsibility of the school, but also the responsibility of the parents. This type of research uses descriptive quantitative research. The results of the study are used to show parental participation in education, especially in contributing to educational institutions. Because parents are the main factor in achieving the education process. With the support and cooperation of all parties in order to realize the common goal of improving the quality of education. Because to create quality students, a quality education is needed as well.